Characterization of a silicon nitride ceramic material for ceramic springs. Issue 10 (August 2020) - Khader, Iyas; Koplin, Christof; Schröder, Christian; Stockmann, Jens; Beckert, Wieland; Kunz, Willy; Kailer, Andreas
Abstract: Under extreme working conditions such as high temperature, strong electric and magnetic fields and acidic or basic environments, ceramic springs offer a clear advantage over conventional steel springs. In this study, a tailored grade of silicon nitride ceramic was characterized as spring material. The basic characterization was complemented with component tests. Bend bars, helical springs and conical disk springs were manufactured and tested under various loading scenarios. Manifested by the smallest effective volume of the three tested geometries, helical springs showed the highest fatigue strength. Nevertheless, the complexity involved in manufacturing helical springs pertaining to their geometrical features resulted in a relatively large scatter in fatigue data. The results pointed out the importance of proper design and machining of the contact surface edges in disk springs, which bear the highest stresses. This work demonstrates the potential of producing ceramic springs with broad applicability and sufficient strength and fatigue resistance.